Analisis Maqasid Syariah Terhadap Sistem Jaminan Sosial Dalam Program Keluarga Harapan - Syaukani, M (Ameena Journal, 2023)
Family Hope Program is a government program that aims to alleviate poverty and prosper the poor. In a research which study the value of Maqasid Sharia (Islamic Purposed Law) that exist in the Family Hope Program. The problems of this research is the social assurance system that is applied through Family Hope Program have not been thoroughly fulfilled to a poor family that exists in Simpang Mamplam, however the Family Hope Program is already suitable in Maqasid Sharia. The purpose of this research is to find out the social assurance system in Islamic economics; to understand the observation of maqasid sharia in Family Hope Program. This research using the method of field research which is a study that can take any preferred data that will be found directly in the field. This research obtain the data directly from the respondent through observation and interview which is arranged in accordance with the research objectives. This research using analysis descriptive methods, a research which known as descriptive and interpreting the actual data. The results which obtained by the researcher in Family Hope Program in Simpang Mamplam are: The social assurance system in Islamic economics itself has four forms such as: Individual assurance, family assurance, society assurance, and the assurance of the State. Family Hope Program focused on the basic needs of society such as primer necessities, health, and education, obligatory is provided by the State free of charge for all people. The review of maqasid sharia in Family Hope Programs is already seen that The Family Hope Program is a program that suitable with maqasid sharia (islamic purposed law), because the program contained by elements that reducing the burden of human’s life specifically in social welfare fields, health and education, which in maqasid sharia stated as the benefits in humans.